Analysis of Fatigue Life of PMMA at Different Frequencies Based on a New Damage Mechanics Model. (11th June 2014) - Huang, Aifeng; Yao, Weixing; Chen, Fang
Abstract : Low-cycle fatigue tests at different frequencies and creep tests under different stress levels of Plexiglas Resist 45 were conducted. Correspondingly, the creep fracture time, S -N curves, cyclic creep, and hysteresis loop were obtained. These results showed that the fatigue life increases with frequency at low frequency domain. After analysis, it was found that fatigue life is dependent on the load rate and is affected by the creep damage. In addition, a new continuum damage mechanics (CDM) model was established to analyze creep-fatigue life, where the damage increment nonlinear summation rule was proposed and the frequency modification was made on the fatigue damage evolution equation. Differential evolution (DE) algorithm was employed to determine the parameters within the model. The proposed model described fatigue life under different frequencies, and the calculated results agreed well with the experimental results.